A developmental theory for Aristotelian practical intelligence. Issue 1 (2nd January 2020) - Ferkany, Matt
Abstract: In Aristotelian virtue theories, phronesis is foundational to being good, but to date accounts of how this particularly important virtue can emerge are sketchy. This article plumbs recent thinking in Aristotelian virtue ethics and developmental theorizing to explore how far its emergence can be understood developmentally, i.e., in terms of the growth in ordinary conditions of underlying psychological capacities, dispositions, and the like. The purpose is not to explicate Aristotle, nor to assimilate Aristotelian ideas to cognitive developmental moral theorizing, but to draw on both to build an independently plausible theory of practical intelligence and its development. It is argued that one fruitful direction attends to the psychology of virtues Aristotle associates with practical intelligence, including comprehension, understanding, sense, and cleverness, instead of Aristotle's remarks distinguishing fully virtuous persons from the continent, incontinent and the many.